2017
DOI: 10.1161/jaha.116.005357
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor‐β Receptor III is a Potential Regulator of Ischemia‐Induced Cardiomyocyte Apoptosis

Abstract: BackgroundMyocardial infarction (MI) is often accompanied by cardiomyocyte apoptosis, which decreases heart function and leads to an increased risk of heart failure. The aim of this study was to examine the effects of transforming growth factor‐β receptor III (TGFβR3) on cardiomyocyte apoptosis during MI.Methods and ResultsAn MI mouse model was established by left anterior descending coronary artery ligation. Cell viability, apoptosis, TGFβR3, and mitogen‐activated protein kinase signaling were assessed by met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Due to a loss of terminally differentiated cardiomyocytes, which is dedicated to wall thinning, ventricular dilatation and fibrosis, apoptosis is a critical contributor to heart failure. It has been reported that TGFβR3 protected ischemia-induced cardiomyocyte apoptosis via activation p38 signaling pathway, whereas loss of TGFβR3 reduced apoptosis and improved cardiac function [37]. Our recently published study verified that EndoA2 attenuated H2O2-induced rat basilar artery smooth muscle cell apoptosis [18].…”
Section: Discussionsupporting
confidence: 70%
“…Due to a loss of terminally differentiated cardiomyocytes, which is dedicated to wall thinning, ventricular dilatation and fibrosis, apoptosis is a critical contributor to heart failure. It has been reported that TGFβR3 protected ischemia-induced cardiomyocyte apoptosis via activation p38 signaling pathway, whereas loss of TGFβR3 reduced apoptosis and improved cardiac function [37]. Our recently published study verified that EndoA2 attenuated H2O2-induced rat basilar artery smooth muscle cell apoptosis [18].…”
Section: Discussionsupporting
confidence: 70%
“…Then, the supernatant was discarded and 150 μL of DMSO was added to dissolve the formazan crystals. The microplate reader (BioTek, USA) was used to measure absorbance value at 490 nm …”
Section: Methodsmentioning
confidence: 99%
“…To investigate the role of RNF4 in heart disease, GFP‐labelled AAV9‐shRNA targeting RNF4 was delivered into the heart to specifically knockdown cardiac endogenous RNF4 via in vivo adeno‐associated virus infection, which is a well‐established experimental technique used in cardiovascular research 20‐22 . After two weeks, successful infection was demonstrated by green‐stained myocardia in the Scramble‐ and shRNF4‐treated groups (Figure ), and endogenous RNF4 was reduced by 41% compared with that of the Scramble group (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%